El anublo bacterial de la yuca (Manihot esculenta Crantz) en America: Etiologia, epidemiologia y control - Lozano, J.C. (1974)
Bacterial wilt of cassava (Manihot esculenta) is the most serious disease in Central and South America, and it has recently been reported in Africa. The symptoms are foliage lesions, dieback, exudation of gum from the young sprouts, and vascular necrosis of stems and roots of susceptible cultivars. The disease spreads readily in the field through rain splashing. The dissemination from one area to another occurs through the planting of infected cuttings and by tools. Satisfactory control of the disease was obtained with the use of resistant varieties and with certified seed obtained from healthy young sprouts. (AS)